Consilia sapientis amici: Saint Thomas Aquinas on the foundation of the evangelical counsels in theological anthropology - Deák, Viktória Hedvig (Tesi gregoriana, 2014)
In modern theological discourse, and more particularly, in theological anthropology, the evangelical counsels are rarely presented as integral parts of the human person's vocation in grace. Rather, theology after the Council of Trent preferred to speak about the counsels as optional obligations, taken up over the commandments, as an area of the greater generosity of those who strive for more perfection. This is why the fundamental question this work poses is: how can we formulate an instrinsic bond between poverty, chastity and obedience, and the human person's vocation in grace? This is a question addressed to Saint Thomas Aquinas, as the first theologian to offer a systematic theology of religious life, whose theological vision predates the modern separation between human and divine, and between the different branches of the theological science. The Angelic Doctor situates the counsels into the dynamism of the virtue of charity which is not a static entity but implies a spiritual development. The counsels are identified as a stage of spiritual generosity and a sign of growth in charity: in a certain way, they concern every Christian. Then, according to Aquinas, the proper context of the counsels is the New Law of graced freedom: the counsels arise from the wisdom and love of Christ, the wise friend, who invites everyone to the perfection of love. These two aspects allow for a remarkably different perception of the counsels than merely optional obligations.